Mechanisms of Ions Adsorption by Nanodiamonds in Aqueous Suspensions - K.A. Laptinskiy; S.A. Burikov; T.V. Laptinskaya; J.M. Rosenholm; O.A. Shenderova; I.I. Vlasov; T.A. Dolenko (Журнал нано- та електронної фізики)
This work is devoted to the study of adsorption properties and adsorption mechanisms of the original (I6), modified (I6COOH) nanodiamonds and charcoal dispersed in water, with respect to dissolved ions (Cu2 +, Pb2 +, NO3 –, CH3COO –) using optical spectroscopy methods: Raman and IR spectroscopies, absorption, dynamic light scattering. Mechanisms of anions and cations adsorption were studied.